Challenges in Parkinson's Disease - Dorszewska, Jolanta; Kozubski, Wojciech (IntechOpen, 2016)
Parkinson's disease is a common neurological disease and affects 2% population of more than 65 years of age and 5% more than 85 years of age. Pathomechanism of this disease is still not fully understood. This book is a sum up of knowledge on the genetic factors and neuronal death mechanisms induced by excitotoxic and inflammatory agents. The authors summarize the pathophysiology observed both in patients with Parkinson's disease and in experimental models. The book also contains the latest views on drug therapy used in the treatment of parkinsonism and other therapeutic approaches for Parkinson's disease. The book ''Challenges in Parkinson's Disease'' was made as a compendium on contemporary challenges in Parkinson's disease.